DEVELOPMENT OF ANDROID-BASED LEARNING MEDIA TO IMPROVE STUDENT UNDERSTANDING IN DIESEL MOTOR COURSES - Khoer, Miftahul; Mubarak, Ibnu; Al Gifari, Muhamad Maris (Universitas Pendidikan Indonesia, 2021)
This study aims to create an android-based learning media that is feasible to be applied in research and used in assisting the learning process and to determine the effect of using learning media in increasing student understanding of Diesel Motor courses, this is because face-to-face learning is replaced by online learning The two-way learning process is difficult to do and causes a lack of understanding of students regarding Diesel Motor courses, to overcome this, interesting and interactive learning media are needed. The method in this study uses RD (Research and Development) with a learning media development model in the form of ADDIE (Analysis, Design, Development, Implementation, Evaluation), and uses aresearch one group pretest posttest design. The sample in this study used a purposive sampling technique with the research subject of 2019 Automotive Engineering Education undergraduate students who were contracting Diesel Motor courses, researchers took a sample of 40 people. The learning media products that have been made are suitable for use based on the validation of material experts and media experts with very feasible categories. The results of this study indicate an increase in learning outcomes when viewed from the average pre-test score of 31.20 and the average post-test score of 37.80 as well as the acquisition of a significance test using the t-test (Paired Sample t-test). with a significance value of 0.000, this increase is caused by the use of learning media that has been made, so the use of this learning media has a good impact in increasing student understanding of the Diesel motor course, in addition, this learning media also adds insight to students in using technology, especially Android for learning purposes.